Drug Resistance in Cancer Cells - Siddik, Zahid H.; Mehta, Kapil; SpringerLink (Online service) (New York, NY : Springer US, 2009)
An estimated 1.5 million patients in the United States are diagnosed with cancer every year and over half-a-million individuals die of the disease. Since the vast majority of the deaths occur after medical intervention with anticancer therapy, both conventional chemotherapy and novel targeted therapy, it can be concluded that these patients die from drug resistant cancers. A growing number of studies have revealed that mechanisms underlying the development of drug resistance in cancer cells are manifold and complex and very likely are dependent on cell and microenvironment context. In view of these facts, it is important to document the mechanisms of drug resistance and understand which are the dominant resistance pathways in a particular tumor type that could provide potential therapeutic targets in a clinical setting. This book serves as a single source for the current knowledge on genetic and epigenetic alterations that contribute to the development of drug resistance. Comprehensive reviews written by renowned experts provide great insight on the current knowledge on drug resistance mechanisms. This book is a ready source of information to clinicians, cell and cancer biologists and defines molecular drug resistance mechanisms that are challenging scientists and clinical oncologists today. About Editors: Dr. Kapil Mehta is a Professor in the Department of Experimental Therapeutics, The University of Texas M. D Anderson Cancer Center, Houston, TX. He has published widely and received several patents on novel discoveries relating to drug resistance in the field of cancer therapeutics. Dr. Zahid H. Siddik is also a Professor in the Department of Experimental Therapeutics at The University of Texas M.D. Anderson Cancer Center. He has studied extensively the mechanisms of drug action and resistance, and is recognized for his seminal studies with platinum-based antitumor agents.
Multidrug Resistance Mediated by MDR-ABC Transporters -- Metastasis and Drug Resistance -- The Role of Autophagy and Apoptosis in the Drug Resistance of Cancer -- Mechanisms of Resistance to Targeted Tyrosine Kinase Inhibitors -- Targeting Transglutaminase-2 to Overcome Chemoresistance in Cancer Cells -- Extracellular Matrix-Mediated Drug Resistance -- Oxidative Stress and Drug Resistance in Cancer -- Nuclear Factor-?B and Chemoresistance: How Intertwined Are They? -- Drug Resistance and the Tumor Suppressor p53: The Paradox of Wild-Type Genotype in Chemorefractory Cancers -- Resistance to Differentiation Therapy -- MicroRNAs and Drug Resistance -- Molecular Signatures of Drug Resistance -- Assessment of Drug Resistance in Anticancer Therapy by Nuclear Imaging -- Overcoming Drug Resistance by Phytochemicals.
Keywords: MEDICINE; ONCOLOGY; TOXICOLOGY; BIOMEDICINE; CANCER RESEARCH; PHARMACOLOGY/TOXICOLOGY.